Prenatal genetic diagnosis of cranioectodermal dysplasia in a Polish family with compound heterozygous variants in WDR35. Issue 10 (17th August 2020) - Walczak‐Sztulpa, Joanna; Wawrocka, Anna; Leszczynska, Beata; Mikulska, Boyana; Arts, Heleen H.; Bukowska‐Olech, Ewelina; Daniel, Maria; Krawczynski, Maciej R.; Latos‐Bielenska, Anna; Obersztyn, Ewa
Abstract: The ciliary chondrodysplasias represent a group of clinically and genetically heterogeneous disorders that affect skeleton development. Cilia are organelles that project from the surface of many cell types and play an important role during prenatal and postnatal human development. Cranioectodermal dysplasia (Sensenbrenner syndrome, CED) is a ciliopathy primarily characterized by craniofacial, skeletal, and ectodermal abnormalities. To date six genes have been associated with CED: IFT122, WDR35, WDR19, IFT140, IFT43, and IFT52 . Prenatal diagnosis of CED is challenging, and genetic testing can facilitate making a correct diagnosis. Here, we report on a family with two male siblings affected by CED: a 3.5 year‐old patient and his 2 year‐old brother. Molecular analysis of the proband at 1 year of age revealed compound heterozygous variants in WDR35 : c.3G>A [p.(Met1‐Ala30delinsMetfsTer4)] and c.2522A>T [p.(Asp841Val)]. Ultrasound examination during the second pregnancy revealed an increased nuchal translucency of 4.5 mm and a hypoplastic nasal bone at 12 weeks of gestation. Prenatal diagnostic testing was offered because of an increased risk for chromosomal abnormalities and recurrence risk for CED. Prenatal genetic analysis of a chorionic villus sample detected the WDR35 variants previously identified in the elder brother. This is the first report of a prenatal genetic diagnosis in CED.